Preoperative Stellate Ganglion Block for Perioperative Pain in Lateralized Head and Neck Cancer: Preliminary Results. (January 2020) - Sharbel, Daniel; Singh, Paramvir; Blumenthal, Daniel; Sullivan, James; Dua, Anterpreet; Albergotti, W. Greer; Groves, Michael; Byrd, J. Kenneth
Patients with head and neck cancer represent a vulnerable population at particular risk of opioid dependence due to frequent histories of substance abuse, requirement of extensive surgery, and the synergistic toxicity of multimodal therapy. Regional anesthetic techniques have been used by other surgical disciplines to facilitate early recovery after surgery and decrease postoperative patient narcotic requirements. This pilot study investigates the efficacy of a preoperative regional analgesia using stellate ganglion block in lateralized head and neck cancer surgery. From our early results, stellate ganglion blockade may hold promise as an effective preoperative intervention for controlling early postoperative pain, lessening narcotic requirements, and improving quality of life.